1998
DOI: 10.1172/jci915
|View full text |Cite
|
Sign up to set email alerts
|

Genetic predisposition to the metabolism of irinotecan (CPT-11). Role of uridine diphosphate glucuronosyltransferase isoform 1A1 in the glucuronidation of its active metabolite (SN-38) in human liver microsomes.

Abstract: Irinotecan (CPT-11) is a promising antitumor agent, recently approved for use in patients with metastatic colorectal cancer. Its active metabolite, SN-38, is glucuronidated by hepatic uridine diphosphate glucuronosyltransferases (UGTs). The major dose-limiting toxicity of irinotecan therapy is diarrhea, which is believed to be secondary to the biliary excretion of SN-38, the extent of which is determined by SN-38 glucuronidation. The purpose of this study was to identify the specific isoform of UGT involved in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

14
382
1
3

Year Published

2000
2000
2008
2008

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 618 publications
(400 citation statements)
references
References 34 publications
14
382
1
3
Order By: Relevance
“…[119][120][121] Polymorphisms of the UGT1A1 Gene as Risk Factors for Drug-Induced Toxicity Patients affected by Gilbert's syndrome display lower glucuronidation rates for a number of therapeutic drugs including acetaminophen, tolbutamide and lorazepam. [20][21][22][34][35][36][37] Since Gilbert's syndrome is associated with the UGT1A1*28 (TA 7 polymorphism), it is more likely that patients with this allele will present an altered drug clearance compared to patients with the wild-type genotype. However, a correlation between the presence of variant UGT1A1 alleles and altered rates of glucuronidation has not been systematically demonstrated.…”
Section: Ugt1a1mentioning
confidence: 99%
See 2 more Smart Citations
“…[119][120][121] Polymorphisms of the UGT1A1 Gene as Risk Factors for Drug-Induced Toxicity Patients affected by Gilbert's syndrome display lower glucuronidation rates for a number of therapeutic drugs including acetaminophen, tolbutamide and lorazepam. [20][21][22][34][35][36][37] Since Gilbert's syndrome is associated with the UGT1A1*28 (TA 7 polymorphism), it is more likely that patients with this allele will present an altered drug clearance compared to patients with the wild-type genotype. However, a correlation between the presence of variant UGT1A1 alleles and altered rates of glucuronidation has not been systematically demonstrated.…”
Section: Ugt1a1mentioning
confidence: 99%
“…CPT-11 is biotransformed by carboxylesterases into a pharmacologically active metabolite, SN-38 (7-ethyl-10-hydroxycamptothecin), 123 which is responsible for severe toxicity. SN-38 undergoes significant glucuronidation to form the corresponding inactive glucuronide (10-O-glucuronyl-SN-38 (SN-38-G)) 124 and UGT1A1 isoenzyme was suggested to be the predominant human UGT involved in the formation of SN-38-G. 35 Individuals with Gilbert's syndrome are at greater risk to experience irinotecaninduced toxicity. 37 Therefore, inherited differences in irinotecan glucuronidating capacity, such as those caused by UGT1A1 promoter polymorphisms, may have an important influence on the pharmacokinetics, the pharmacologic effects and toxicity of this drug.…”
Section: Ugt1a1mentioning
confidence: 99%
See 1 more Smart Citation
“…[13][14][15] While the primary selective pressure for UGT1A enzyme function may have been metabolism of endogenous molecules, UGT1A function is necessary for elimination of exogenous compounds such as the anti-cancer drug irinotecan. [16][17][18] The same common UGT1A1 variants associated with mild elevations of serum bilirubin are associated with diminished in vitro glucuronidation of the active irinotecan metabolite, SN-38, [19][20][21][22] and prolonged exposure and increased toxicity in patients receiving this agent. [23][24][25] As shown by Sai et al, 25 re-sequencing of the UGT1A1 gene in 85 Japanese patients treated with irinotecan confirmed that the haplotypes containing lower expression variants were associated with both a low SN-38G/SN-38 AUC ratio and elevated pretreatment bilirubin concentration.…”
Section: Introductionmentioning
confidence: 99%
“…CPT-11 is a prodrug that requires activation to the active metabolite, 7-ethyl-10-hydroxycamptothecin (SN-38), which is approximately 100-to 1000-fold more active than the parent drug (Hertzberg et al, 1989). A host of enzymes, including carboxylesterases to form SN-38 (Humerickhouse et al, 2000), UDP glucuronosyltransferases mediating SN-38 glucuronidation to form the b-glucuronic acid conjugate, SN-38G, (Iyer et al, 1998), intestinal and endogenous b-glucuronidases causing deconjugation of SN-38G (Sparreboom et al, 1998; Slatter et al, 2000), as well as cytochrome P-450 isoforms (Haaz et al, 1999;Santos et al, 2000) to form APC and NPC are involved in CPT-11 metabolism. In addition, several drug-transporting proteins, notably a canalicular multispecific organic anion transporter (cMOAT) located on the bile canalicular membrane (Chu et al, 1998), and P-glycoprotein (Chu et al, 1999), can influence CPT-11 elimination through hepatobiliary secretion and intestinal (re-)absorption.…”
mentioning
confidence: 99%